Gender Disparities in Adjusted Per Capita Expenditure: A Comparative Study of Samarinda and Yogyakarta - Wedi Aningrum, Wahyu; Teguh Prakoso, Cathas; Indarto, Kus (Universitas Muhammadiyah Makassar, 2026)
This study aims to examine gender disparities in adjusted per capita expenditure by comparing Samarinda and Yogyakarta, with particular attention to how local economic structures, women’s labor-market participation, and gender-responsive governance shape different patterns of inequality. The study employed a qualitative comparative case-study design. Primary data were obtained through interviews with policy actors in women’s empowerment, labor, cooperatives, micro, small, and medium enterprises, and regional planning, while secondary data were drawn from official statistical publications, regional planning documents, and gender-mainstreaming policy reports. Data were analyzed using the interactive model of data reduction, data display, and conclusion drawing, followed by cross-case comparison. The findings suggest that the wider gender gap in Samarinda is driven by lower female labor force participation, the concentration of women in unpaid domestic and informal work, limited access to formal employment and productive resources, and the uneven implementation of gender-responsive planning and budgeting. In contrast, Yogyakarta’s narrower gap is supported by a service-based economy that provides broader opportunities for women’s participation and stronger inter-agency coordination in gender-responsive policy implementation. The study emphasizes the need for affirmative local policies that expand women’s access to employment, social protection, productive resources, and institutionalized gender-responsive governance. This study contributes to gender and public administration scholarship by offering a city-level comparative analysis that links adjusted per capita expenditure disparities with structural gender relations, local economic configuration, and institutional capacity.